COMPARATIVE STUDY OF LAZISMU AND ACT PROMOTION METHODS IN MEDAN CITY - Rianto, Hartato; Aseandi, Riski (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2020)
Abstract The purpose of this study was to compare the promotional methods applied by LAZISMU with ACT in Medan City. Analyzing the amount of costs used to carry out promotional activities, as well as the impact of the promotions carried out. This research is a qualitative research with descriptive analysis method. The data collection method in this study used indirect interviews using telephone lines to prevent transmission of COVID 19. The results of this study indicate that LAZISMU and ACT have different branding tendencies. This difference is because the two zakat management organizations have different positioning. LAZISMU is affiliated with a leading community organization in Indonesia, namely Muhammadiyah so that LAZISMU can mobilize all available resources within Muhammadiyah to support LAZSMU's performance. ACT, which is not affiliated with any mass organization, has more free space. ACT makes optimal use of all its resources so that it can get maximum results later. ACT makes humanitarian issues such as disasters a main brand in its marketing practices, while LAZISMU focuses more on routine humanitarian programs. The marketing method applied is to reduce the costs required for promotion. These two LAZs state that the marketing practices carried out so far have had quite a positive impact on the sustainability of LAZIS activities.